أثر القيم التنظيمية على بناء منظمة متعلمة من وجهة نظر موظفي مديرية الصيانة سوناطراك الاغواط: The impact of organizational values on building a learning organization from the point of view of the employees of the Maintenance Directorate Sonatrach Laghouat - طبراخ يوسف; عبدلي لطيفة (Journal of North African Economies, 2025)
This study aimed to identify the role of the dimensions of organizational values in building the learning organization from the perspective of employees of the Sonatrach Maintenance Directorate Laghouat, the study community is composed of all employees of Directorate and numbered (286), A sample of (60) employees was selected, the questionnaire, which included (48) a paragraph, was designed as the main tool for collecting information from the study sample, of which (49) were retrieved. After statistical treatment based on the SPSS program, it was confirmed that there is a statistical significant relationship of organizational values in its various dimensions in building the learning organization at the significance level (5%(.